Transformational Leadership dan Job Satisfaction Variabel A As Factor That Decrease Organizational Citizenship Behavior of Nurses in Private Hospitals in Manado City - Vinno Petrus Manoppo; Endang Siti Astuti; Kusdi Raharjo; Andriani Kusumawati (Wacana Journal of Social and Humanity Studies, 2021)
The purpose of this study was to examine and explain transformational leadership variables that affect job satisfaction variables, transformational leadership variables that affect organizational citizenship behavior, job satisfaction variables that affect organizational citizenship behavior. The population of this study was all nurses in four (4) private hospitals in the city of Manado as many as 522 people. Sample size 227 people. The sampling technique uses Proportional Random Sampling. The data analysis technique used is Generalized Structured Component Analysis (GSCA). GeSCA Analysis Tool. The results of this study state that Transformational leadership has a positive effect on job satisfaction and transformational leadership has a positive significant effect on organizational citizenship behavior. Job satisfaction has a positive significant effect on organizational citizenship behavior.